ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI POSITIF WORD OF MOUTH (STUDI PADA KONSUMEN PT. ASIASURYA JAYARAYA IV PURWOSARI PASURUAN) - Amma Fazizah; Merry Tri Utami (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
The purpose of this study is to explain and determine the effect of Service Quality, Product Quality, Customer Satisfaction and Customer Experience on Positive Words of Mouth, no matter what the effect of Service Quality, Product Quality, Customer Satisfaction and Customer Experience on Positive Word of Mouth and which ones dominant influence between Service Quality, Product Quality, Customer Satisfaction and Customer Experience to Positive Word of Mouth simultaneously and partially. The sample selection technique used purposive sampling and the respondents were determined by 296 people. The results showed that: 1) all variables had a positive effect on the independent variable except for customer satisfaction, 2) Service quality had an effect of 4.426%, product quality had an effect of 2.684%, customer experience had an effect of 4.875%. Customer satisfaction has no positive effect but is equal to -0.393%, 3) Customer experience is more dominant, because the significant value of customer experience is 0.000 less than 0.05 and the value of T count is 4.875 from T table 0.138. The next variable is the level of influence under the customer experience variable.